Aberrant protein palmitoylation: A new route involved in Alzheimer's disease. (December 2021) - Fusco, Salvatore; Natale, Francesca; Gulisano, Walter; Spinelli, Matteo; Rinaudo, Marco; Aceto, Giuseppe; Greca, Francesco; Puzzo, Daniela; Grassi, Claudio
Abstract: Background: Growing evidence points to altered metabolic signals as a risk factor for Alzheimer's disease (AD). The high fatty acid levels and brain insulin resistance (BIR) found in AD brains may impinge on protein palmitoylation (P‐S‐palm), a post‐translational modification critically involved in the regulation of neuronal protein localization and synaptic function. Our previous findings highlighted the critical role of aberrant palmitoylation in BIR‐dependent memory impairment (Spinelli et al., 2017). Method: We tested the effect of chronic intranasal injection of the palmitoylation inhibitor 2‐bromopalmitate (2BP) on a large cohort of male and female 3xTg‐AD mice, starting from 3 months of age, by performing cognitive (novel object recognition and object displacement tests), electrophysiological (LTP), immunohistochemical (Abeta deposition) and molecular analyses (Abeta measurement by ELISA). We also analyzed the palmitoyl‐proteome (by acyl biotin exchange assay and mass‐spectrometry) in the hippocampus of 9‐month‐old wild type, 3xTg‐AD and 2BP‐treated 3xTg‐AD mice. Result: 2BP delayed the onset of memory deficits in both male and female 3xTg‐AD mice. More importantly, 2BP significantly enhanced cognitive performances in 6‐, 9‐ and 12‐month‐old animals. Accordingly, electrophysiological analyses on hippocampal brain slices from 2BP‐treated 3xTg‐AD mice revealed greater long‐term potentiation at CA3‐CA1 synapses. In addition, 2BP mice showed lower Abeta deposition in hippocampus. Finally, palmitoyl‐proteome analysis revealed a large number of proteins involved in APP and tau metabolism, synaptic plasticity and brain metabolism aberrantly palmitoylated in the AD mouse model and reverted by 2BP. Conclusion: Our data indicate that aberrant palmitoylation plays a critical role in the onset and progression of AD and reveal novel targets of protein palmitoylation potentially involved in the development of neurodegeneration and dementia. This is also the first preclinical study on the effect of 2BP on AD‐related cognitive decline.